Adolescent exergame play for weight loss and psychosocial improvement: A controlled physical activity intervention1. (17th April 2013) - Staiano, Amanda E.; Abraham, Anisha A.; Calvert, Sandra L.
Abstract Overweight and obese youth, who face increased risk of medical complications including heart disease and type II diabetes, can benefit from sustainable physical activity interventions that result in weight loss. Objective: This study examined whether a 20‐week exergame (i.e., videogame that requires gross motor activity) intervention can produce weight loss and improve psychosocial outcomes for 54 overweight and obese African‐American adolescents. Design and Methods: Participants were recruited from a public high school and randomly assigned to competitive exergame, cooperative exergame, or control conditions. All exergame participants were encouraged to play the Nintendo Wii Active game for 30‐60 min per school day in a lunch‐time or after‐school program. Cooperative exergame participants worked with a peer to expend calories and earn points together, whereas competitive exergame participants competed against a peer. Control participants continued regular daily activities. Outcome measures included changes in weight, peer support, self‐efficacy, and self‐esteem, measured at baseline, and at ∼10 and 20 weeks. Results: Growth curve analysis revealed that cooperative exergame players lost significantly more weight (mean = 1.65 kg; s.d. = 4.52) than the control group, which did not lose weight. The competitive exergame players did not differ significantly from the other conditions. Cooperative exergame players also significantly increased in self‐efficacy compared to the control group, and both exergame conditions significantly increased in peer support more than the control group. Conclusion: Exergames, especially played cooperatively, can be an effective technological tool for weight loss among youth.